Monitoring of proper formation of motor skills of swimming in men and women in the World Championships on water sports for the I-II stages of 1973-2019 - Ganchar, O.; Ganchar, I.; Ciorba, C.; Medynsky, S.; Arkhipov, A.; Chernyavskyi, O.; Cherkun, I. (Science, Movement & Health, 2021)
The International Swimming Federation - FINA, almost always includes styles of swimming in the world swimming Championships program. So far, with the 1973-2019 there has been almost 18 world swimming Championships, the program of which was sporting and marathon swimming. It is therefore very important to know the real assessment of the participants of prestigious competitions to determine the real condition of the development of styles of swimming among young people of different age. The purpose of the research is to determine the level and degree of formation of motor skills of swimming by swimmers-winners based on monitoring of the final results of the world's swim on all the Championships of the water sports that have occurred since 1973-2019. It is found out with men and women of different ages at 8 Championships of the world swimming on the I stage in 1973-1991, and among 10 facts on the II stage in 1993-2019. Material. The results of the finalists were compiled and analyzed at the I stage in 1973-1998: Among 390 men and 366 women, who became the winners of these prestigious competitions in the World Championships water sports, including swimming. At the II stage of the world swimming Championships in 2001-2019, the state of the motor skills of swimming, which was found out among 723 men and 702 women, who received gold, silver and bronze medals among the strongest swimmers-winners in the world. Results. For the first time the dynamics was found out of reliable formation of motor skills of swimming with the ability of overcoming different ways of swimming depending on gender difference of participants at age over 21-20 (men, x ± m = 21,42 ± 1, 25; women, x ± m = 19,95 ± 1,84; t = 0,02, p > 0,05) final starts on the I stage of the world swimming Championships in 1973-1998, and the total difference of average swimming speed is over - 0,16 m/s (men, x ± m = 1,71 ± 0,16; women, x ± m = 1,55 ± 0,14; t = 5,17, p < 0,05). First of all, the dynamics of the formation of motor skills of swimming on the ability of mastering different styles of swimming depending on gender difference of participants at age 25-23 (men, x ± m = 25,28 ± 1,10; women, x ± m = 22,73 ± 1,27; t = 2,27, p < 0,05) at the II stage of the world swimming Championships in 2001-2019, and the total difference of the average speed of swimming is over - 0.17 m/s (men, x ± m = 1,80 ± 0,18; women, x ± m = 1,63 ± 0,15; t = 3,29, p < 0,05). Conclusions. The received data will make a substantial professional and informational contribution to further improvement of the existing system of physical education and sports in a gender-sensitive approach to the training of youth and their improvement in physical raising and sport. This will be useful for finding out the rating of performance of the strongest swimmers on the example of prestigious competitions, which are certainly indicators at the summer final starts of swimming at all the world swimming Championships in 1973-1999 on the I stage, as well as on II Stage in 2001-2019. This also details trends of gradual long-term development of the formation of motor skills of swimming among young people of different age.